Efeito imediato da estimulação transcraniana por corrente contínua associada ao exercicio aeróbico sobre a variabilidade da frequência cardíaca em indivíduos pós acidente vascular cerebral: ensaio clínico, controlado, randomizado, duplo-cego - Heinz, Solange Zilli Lo Presti (2021)
Objective: To evaluate the effect of anodal Transcranial Direct Current Stimulation (TCTE) on the left dorsolateral prefrontal cortex (DLCLC) associated with aerobic exercise (AE) on Heart Rate Variability (HRV), distance traveled on an ergometric bicycle and subjective perception of effort of individuals after chronic stroke. Methodology: Clinical, randomized, controlled and double-blind trial with 17 individuals, randomized into 2 groups: anodal tDCS (aETCC) and sham (sETCC) plus AE. The HRV was evaluated for 15 minutes at rest and after one session, and the distance walked together with the subjective perception of post-AE effort. Interventions: tDCS with anode electrode in left LMPLC, cathode in supraorbital region contralateral to the anode, for 20 minutes associated with AS. Data Analysis: HRV assessed by variance, rMSSD, low and high absolute frequency and sympathovagal balance, as well as distance covered and subjective perception of exertion, using the Mann-Whitney and independent-sample t tests. Results: Under baseline conditions, the groups showed greater vagal performance. After the TSCC and EA session, there was no significant difference in HRV, and after anodal and sham intervention, both groups maintained a predominance of performance. In the distance covered, with no significant difference, the active person covered 156 meters more than the sham, while the subjective perception of respiratory effort and lower limbs was greater for the sham. Conclusion: The study demonstrated that anodal tDCS in left LMPLC associated with AS did not promote significant changes in the modulation of the autonomic nervous system, optimizing vagal action. The performance of the distance covered, although better for the anodal group, had no clinical importance in this sample.